Enhancing Cognitive Development of Stunted Children through Sensory Modalities: Evidence from Mataram, Indonesia - Zaenab, Siti; Wiguna, Ida Bagus Alit Arta (Institut Agama Hindu Negeri Gde Pudja Mataram, 2025)
Stunting is a chronic nutritional problem that is still a serious concern in Indonesia, especially in West Nusa Tenggara, where the prevalence reaches more than 30%. In addition to impacting delayed physical growth, stunting also has implications for children's brain and cognitive development, which is characterized by low IQ scores, language delays, and reduced problem-solving skills. This study aims to analyze how sensory modalities can be used to stimulate the brains of stunted children in Mataram, focusing on strategies applied by teachers and parents. The study used a qualitative descriptive approach with a phenomenological design, involving six stunted children at Dwijendra Mataram Kindergarten, as well as supporting data from teachers and parents through observation, structured interviews, documentation, and simple questionnaires. The results indicated that stunted children responded more slowly to visual and auditory tasks but were more adaptive to tactile and kinesthetic stimulation, while 70% of teachers had never received special training and 65% of parents did not understand the importance of sensory-based brain stimulation. These findings confirm that stunting in Mataram is not only influenced by malnutrition, but also by limited stimulation of the human senses, namely the senses of sight, hearing, smell, taste and touch. both at school and at home. The originality of this research lies in the introduction of the concept of modality task fit, which emphasizes the importance of choosing the type of stimulation according to the strength of the sensory pathway of stunted children. This concept contributes to early childhood education and public health by offering a precise, systematic, and effective intervention framework. The study's conclusions emphasized the importance of combining nutritional improvement with multi-sensory-based brain stimulation to optimize the cognitive development of stunted children.